Prescription Pattern Analysis of Antidiabetic Drugs in Patients with Diabetes Mellitus: A Retrospective Observational Study - Saritha, Damineni; Koneru, Anupama; Naqi, Zaina; Anjum, Syeda Sameera (Indian Journal of Pharmacy Practice, 2026)
Diabetes Mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia, associated with significant morbidity and mortality if inadequately managed. Prescription pattern analysis serves as a vital pharmacoepidemiological tool for evaluating real-world drug utilization, rationality of prescribing, and adherence to standard treatment guidelines. To analyse the prescription pattern of antidiabetic drugs, evaluate prescribing trends, classify drug classes, compare monotherapy with combination therapy, and assess the influence of comorbid conditions on drug selection among diabetic patients in Hyderabad, Telangana. A retrospective observational study was conducted using 25 prescriptions collected from KIMS Hospital, Srinagesh Diabetes and Endocrine Clinic, Caspian Diagnostic Centre, and private clinics in Hyderabad. Demographic and therapeutic data were recorded and analysed using descriptive statistics. The study included 13 males (52%) and 12 females (48%), with age ranging from 39 to 79 years. Combination therapy was prescribed in 60% of cases. The most frequent regimen was sulfonylurea plus metformin (20%), followed by dipeptidyl peptidase-4 inhibitor plus metformin (16%) and insulin monotherapy (16%). Metformin was involved in 72% of prescriptions. Comorbid hypertension was present in 36% of patients. Prescribing patterns largely adhered to evidence-based guidelines, with metformin as the cornerstone and progressive adoption of newer drug classes. Regular prescription audits are recommended to promote rational drug use and optimize glycemic outcomes.
Keywords: Antidiabetic Drugs; Combination Therapy; Diabetes Mellitus; Drug Utilization; Metformin